Mobile Alert System For Children Immunization - Elburase, Ebrahem Ali (2008)
Nowadays integration of the new technology for different purpose, need to provide new facilities that satisfy with the users needs. The study proposed the mobile alert system for children immunization to support parents by provide them with the appropriate technology to alert immunization date. For their children rapid growth with the using of mobile services becomes more necessary in various fields especially for those who familiar with the mobile devices. With mobile alert system for children immunization, parents will be able to receive alert messages about the immunization state of their children anytime and anywhere. The proposed system save time and effort of parents to make their immunization check in case of forget the date of the immunization. Mobile alert system for children immunization obtains the easy way to enquire about their children immunization state by the alert messages, that the immunization center provides it.